Superoxide dismutase-embedded metal–organic frameworks via biomimetic mineralization for the treatment of inflammatory bowel disease. Issue 27 (1st July 2022) - Bai, Shaowei; Shao, Xinxin; Tao, Yu; Wang, Song; Han, Haobo; Li, Quanshun
Abstract : Inflammatory bowel disease (IBD) is characterized by chronic and spontaneous inflammation in the gastrointestinal tract, and has been associated with an improved level of reactive oxygen species (ROS). Abstract : Inflammatory bowel disease (IBD) is characterized by chronic and spontaneous inflammation in the gastrointestinal tract, and has been associated with an improved level of reactive oxygen species (ROS). Herein, superoxide dismutase (SOD) was encapsulated into zeolitic imidazolate framework-zni (ZIF-zni) to construct a nanocomposite termed SOD@ZIF-zni through biomimetic mineralization, which was then used as a formulation for the IBD treatment. The SOD@ZIF-zni composite could efficiently suppress the level of ROS and pro-inflammatory cytokines, using the colorectal cancer cell line SW480 as a model. Oral administration of the SOD@ZIF-zni composite could relieve the oxidative stress and inhibit the release of pro-inflammatory cytokines in the inflamed colonic tissues, leading to the alleviation of colitis in dextran sulfate sodium-induced colitis mice. Overall, the favorable therapeutic efficacy and biocompatibility of SOD@ZIF-zni gave it potential to be used as a safe and effective formulation for IBD treatment in the future.